PREBIOTIC TEST OF HYDROLYSIS PRODUCT OF CELLULOSE EXTRACT FROM BANANA LEAVES KEPOK (Musa Paradisiaca Linn) BY β-AMYLASE - Bahri, Syaiful; Tobigo, Siska Shintia; Syamsuddin,; Prismawiryanti, (International Journal of Psychosocial Rehabilitation, 2020)
Banana leaves have one agricultural waste containing high enough cellulose Enzymatically hydrolysis cellulose will produce oligosaccharides and other compounds that have chains shorter. That compounds from hydrolysis processes, in general, can be as a prebiotic compound that can decrease the cell number of Escherichia coli and increase the cell number of Lactobacillus bacteria in the human digestive tract. Based on the information provided, the study was aimed at hydrolysis crude cellulose extract from banana leaves of using enzyme β - amylase and to determine the prebiotic character from hydrolysis banana leaves of banana. The study was conducted by a completely randomized design. Crude cellulose extraction was obtained by process delignification cellulose using NaOH 9%. Crude cellulose extract was hydrolysis by β - amylase enzyme with different hydrolysis temperatures (35, 40, 45, 50 and 55°C) and different hydrolysis time (3, 4, 6 and 7 hours). Test Prebiotic was conducted by method dilution and spread plate, in this case, Escherichia coli was added with solution hydrolysis and was grown on agar nutrient medium. The results showed that at 55°C the cell number of Escherichia coli decreased from 1,2 x 107 to 4 x 105 CFU/ml and the best hydrolysis time was 7 hours where the cell number of Escherichia coli decreased to 3 x 105 CFU/ml.